The Larva of Acanthognathus (Hymenoptera: Formicidae) - George C. Wheeler; Jeanette Wheeler (Psyche: A Journal of Entomology)
In 1953 Brown divided the tribe Dacetini into four subtribes: Dacetiti, Orectognathi, Epopostrumiti and Strumigenitio. After studying the larvae of eight dacetine genera (Daceton, Orectognathus, Epopostruma, Mesostruma, Alistruma, Clarkistruma, Strumigenys and Smithistruma) representing all four subtribes, we concluded (1954) that the larval similarities and differences confirmed the grouping of the adults. But now, alas, our study of the larva of Acanthognathus forces us to revise our conclusion.